Irrigation control based on model predictive control (MPC): Formulation of theory and validation using weather forecast data and AQUACROP model. (April 2016) - Delgoda, Dilini; Malano, Hector; Saleem, Syed K.; Halgamuge, Malka N.
Abstract: This research proposes A THEORETICAL FRAMEWORK based on model predictive control (MPC) for irrigation control to minimize both root zone soil moisture deficit (RZSMD) and irrigation amount under a limited water supply. We (i) investigate means to incorporate direct measurements to MPC (ii) introduce two Robust MPC techniques – Certainty Equivalence control (CE) and Disturbance Affine Feedback Control (DA) – to mitigate the uncertainty of weather forecasts, and (iii) provide conditions to obtain two important theoretical aspects of MPC – feasibility and stability – in the context of irrigation control. Our results show that system identification enables automation while incorporating direct measurements. Both DA and CE minimize RZSMD and irrigation amount under uncertain weather forecasts and always maintain soil moisture above wilting point subject to water availability. The theoretical results are compared against the model AQUACROP, weather data and forecasts from Shepparton, Australia. We also discuss the performance of Robust MPC under different water availability, soil, crop conditions. In general, MPC shows to be a promising tool for irrigation control. Highlights: MPC is used to minimize both root zone soil moisture deficit and irrigation amount. System identification incorporates direct measurements to MPC enabling automation. Uncertainty in weather forecasts is mitigated using two modified Robust MPC approaches. Optimal operation can be guaranteed through the proposed method. Guaranteed operation above wilting point at all times subject to water availability.